2004
DOI: 10.1002/hep.20244
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelin-1 and the endothelin B receptor in the pathogenesis of hepatopulmonary syndrome in the rat

Abstract: Endothelin-1 (ET-1T he endothelium plays a central role in the regulation of vascular tone both under normal circumstances and in cirrhosis by releasing endotheliumderived vasodilators and vasoconstrictors in response to a variety of biochemical and physical stimuli. 1 Nitric oxide (NO) and endothelin-1 (ET-1) are two important endothelial mediators that modulate vascular tone. Endothelial NO production is catalyzed predominately by the endothelial form of nitric oxide synthase (eNOS) and under normal circumst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
112
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 44 publications
9
112
1
5
Order By: Relevance
“…The endothelin-A receptor mediates vasoconstriction and is down-regulated in animal models of HPS, whereas expression of the endothelin-B receptor, which leads to vasodilatation via endothelial nitric oxide synthase, is increased. [35][36][37] Data from animal models of HPS suggest a central role for pulmonary intravascular macrophages through generation of inducible nitric oxide synthase, vascular endothelial growth factor, and platelet-derived growth factor. 35,38,39 Inhibition of nitric oxide synthase, the endothelin-B receptor, and vascular endothelial growth factor has mitigated HPS in animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelin-A receptor mediates vasoconstriction and is down-regulated in animal models of HPS, whereas expression of the endothelin-B receptor, which leads to vasodilatation via endothelial nitric oxide synthase, is increased. [35][36][37] Data from animal models of HPS suggest a central role for pulmonary intravascular macrophages through generation of inducible nitric oxide synthase, vascular endothelial growth factor, and platelet-derived growth factor. 35,38,39 Inhibition of nitric oxide synthase, the endothelin-B receptor, and vascular endothelial growth factor has mitigated HPS in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Data from animal models of HPS suggest a central role for pulmonary intravascular macrophages through generation of inducible nitric oxide synthase, vascular endothelial growth factor, and platelet-derived growth factor. 35,38,39 Inhibition of nitric oxide synthase, the endothelin-B receptor, and vascular endothelial growth factor has mitigated HPS in animal models. [40][41][42] Notably, these same mediators have also been implicated in POPH and endothelin receptor antagonists (dual and selective), and phosphodiesterase-5 inhibitors are mainstays of therapy for PAH and POPH.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 is a peptide with a powerful vasoconstrictor action that is involved in the genesis of several diseases, mainly in the hepato-biliary area. Therefore, it has been suggested that ET-1 has a key function in serious complications of hepatic cirrhosis such as portal hypertension (17) and hepatopulmonary syndrome (18). It was recently shown that the blocking of ET-1 receptors improved microcirculation and sinusoidal perfusion in an experimental model of acute liver failure (19).…”
Section: Discussionmentioning
confidence: 99%
“…Through the tight contact ET-1 enters the circulatory system, binds to ET-receptors in the endothelial cells of the lung vessels, causing increase in the expression and activity of eNOS, and vasodilation [60]. In addition, there is evidence that the introduction of ЕТ В receptor selective antagonist to animals after ligation of the common bile duct causes a reduction in pulmonary endothelial eNOS and improvement of HPS symptoms [61].…”
Section: Endothelin -1 and Endothelin Receptorsmentioning
confidence: 99%